Photophysics of Methylammonium Lead Tribromide Perovskite: Free Carriers, Excitons, and Sub‐Bandgap States. Issue 13 (4th February 2020) - Droseros, Nikolaos; Tsokkou, Demetra; Banerji, Natalie
Abstract: Methylammonium lead tribromide perovskite, one of the first artificially synthesized perovskites, can be used in multijunction solar cells and for light‐emitting applications. Its structure leads to a wide direct bandgap, a high extinction coefficient for absorption, and an exciton binding energy that is higher than the thermal energy at room temperature. The broad range of studies performed on the optical phenomena in this material has revealed the contribution of free carriers, excitons, and defect states to its photoluminescence properties. The present report aims to highlight the role played by the different primary photoexcitations, by defects and a variety of optical phenomena (dual emission, reabsorption, photon‐recycling, Rashba‐splitting) on the observed excited‐state properties of this semiconductor. Focus is given to the manifestation of these properties in different spectroscopic measurements. Abstract : The current report discusses the progress in understanding the intriguing excited‐state properties of methylammonium lead tribromide perovskite. Its high absorption coefficient, the small Stokes shift between the absorption and emission, as well as the coexistence of both photo‐generated free carriers and excitons are only a few of the unique properties that have been spectroscopically revealed for this material.